1991
DOI: 10.1002/hed.2880130414
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bone involvement by prostatic adenocarcinoma: Report of two cases and review of the literature

Abstract: Although axial bone and cranial metastases are common in patients with prostatic carcinoma, temporal bone involvement is rare. We report 2 cases of prostatic adenocarcinoma with temporal bone metastasis and review the relevant literature. One case had a 3-year history of a prostatic carcinoma, whereas in the second case the temporal bone metastasis was the initial presentation. Awareness of the possibility of temporal bone involvement by prostate carcinoma and application of immunohistochemical studies will he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Although temporal bone metastasis may be the first indication of an underlying malignancy, the majority of patients have a known primary with widespread disease [9,10]. In a review of 148 tumors metastatic to the temporal bone, Nelson and Hinojosa [11] observed the five most frequent primary sites to be breast (21%), lung (10%), kidney (7%), prostate (7%), and stomach (5%) (Fig.…”
Section: Ear and Temporal Bonementioning
confidence: 99%
“…Although temporal bone metastasis may be the first indication of an underlying malignancy, the majority of patients have a known primary with widespread disease [9,10]. In a review of 148 tumors metastatic to the temporal bone, Nelson and Hinojosa [11] observed the five most frequent primary sites to be breast (21%), lung (10%), kidney (7%), prostate (7%), and stomach (5%) (Fig.…”
Section: Ear and Temporal Bonementioning
confidence: 99%
“…There are a few reported skull metastatic cases. The other study reported a case of metastatic prostatic adenocarcinoma presenting with parietal bone involvement [5] and other study reported two cases with temporal bone involvement [6]. Occipito-parietal bone metastases of prostate adenocancer have not been reported in the literature before.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant temporal bone tumors can occur because of a primary tumor, local invasion (such as nasopharynx), and distant metastasis (2,3,9). Malignant lesions of the skull base and nasopharynx are more frequent causes of these syndromes (10).…”
Section: Discussionmentioning
confidence: 99%